Experiences of Palestinian patients with hospital services: a mixed-methods study - Mahmoud Radwan; Sahar Hassan; Adel Takruri; Carol El Jabari; Inad Nawajah (BMJ Open Quality)
Background This study aimed at assessing patient experiences with hospital services and key factors associated with better experiences.Methods The study design is cross-sectional supported by qualitative interviews. The Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) was used as data collection instrument. A convenience sample of 391 volunteers aged ≥18 years participated in this study. Qualitative interviews were conducted with patients and healthcare providers to further enrich and explain the quantitative results.Results The average age of the sample was 41.34, SD (16.4), range (18–87). Females represented 61.9% of the whole sample. Almost 75% were from the West Bank and 25% from the Gaza Strip. The majority of respondents reported that doctors and nurses were respectful, listened to them and explained clearly to them always or most of the time. Only 29.4% of respondents were given written information about the symptoms they may have after discharge from the hospital. Factors that were independently associated with higher scores on the HCAHPS scale were; being females (coef: 0.87, 95% CI: 0.157 to 1.587, p=0.017), being healthy (coef: −1.58, 95% CI: −2.458 to −0.706, p=0.000), being with high financial status (coef: 1.51, 95% CI: 0.437 to 2.582, p=0.006), being from Gaza (coef: 1.45, 95% CI: 0.484 to 2.408, p=0.003) and who visited hospitals outside of Palestine (coef: 3.37, 95% CI: 1.812 to 4.934, p=0.000). Overcrowding, weak organisational and management processes, and inadequate supply of goods, medicines, and equipment were reported factors impeding quality services via in-depth interviews.Conclusions The overall hospital experiences of Palestinian patients were moderate but varied significantly based on patients’ factors such as sex, health status, financial status and residency as well as by hospital type. Hospitals in Palestine should invest more in improving their services including communications with patients, the hospital environment and communication with patients.